Rab35-regulated lipid turnover by myotubularins represses mTORC1 activity and controls myelin growth - Linda Sawade; Federica Grandi; Marianna Mignanelli; Genaro Patiño-López; Kerstin Klinkert; Francina Langa-Vives; Roberta Di Guardo; Arnaud Echard; Alessandra Bolino; Volker Haucke (Nature Communications, 2020)
Charcot-Marie-Tooth (CMT) is an inherited peripheral neuropathy. Here, the authors show that Rab35 forms a complex with genes implicated in CMT, MTMR13 and MTMR2, which regulates myelin growth by controlling mTORC1 signaling through lipid turnover.